Pengaruh Pemberian Etanol Peroral terhadap Berat Testis Tikus Putih (Rattus norvegicus Strain Wistar) - Antonius Oktavian; Elieser Elieser; Agnes S. Rahayu; Dais Iswanto (Jurusan Biologi FMIPA Universitas Cenderawasih, 2010)
Alcohol (ethanol) has long been used as liquor. In some areas in Indonesia, the use of ethanol is an insaperable part of family rites and traditional festivities. However, due to its serious consequences, alcoholism becomes a chronic social problem. Ethanol effects the metabolism in body organs and tissues, including male reproductive organ. The objective of this study was to prove that ethanol comsumption may reduce the weight of testis. This study used Posttest Only Group Design with experimental animals of 30 male rats (Wistar strain Rattus norvegicus) that were subjected in five types of treatment, i.e,(1) feeding with aquades 2ml/day as control group (2) feeding with 10% 1 gr/Kg/day of ethanol, (3) feeding with 10% 3gr/Kg/day of ethanol, (4) feeding with 30% 1 gr/Kg/day of ethanol and (5) feeding with 30% 3 gr/Kg/day of ethanol. Treatment was given daily for 45 days. At the end of the study, on the day 46th, the rats was sacrified for examination. Sample of testis were taken for weight examination. Data were analysed using Anova and when the difference was found, the analysis was followed with Least significant Difference at the level of significance of 95%. The result of this study showed that ethanol reduced the weight of testis compared to control. The results of Anova test revealed that higher dosage and concentrations of ethanol resulted in significantly different decrease of the testis’s weight (p<0,05) compared to other dosage and other concetration. In conclusion, ethanol has effect in the reduction of the weight of the testis.Key words: ethanol, male reproduction, Rattus norvegicus, weight of testis.